2012
DOI: 10.1002/jmv.23392
|View full text |Cite
|
Sign up to set email alerts
|

Do different lamivudine‐resistant hepatitis B genotypes carry the same risk of entecavir resistance?

Abstract: Entecavir switch is one of the treatment options for lamivudine-resistant hepatitis B (HBV) patients in Asia. This study examined the outcome of patients with different baseline resistance genotypes in a cohort study. In this study, 14 patients with chronic HBV were treated with entecavir 1 mg/day for 5 years. Enrolment criteria include: documented lamivudine resistant mutations, treatment with adefovir 10 mg/day for at least 24 weeks, and Child-Pugh score <7. Most had previous failed adefovir therapy and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, in case of ETV utilization in patients with LAM treatment failure, the development of ETV resistance is more to be expected. Recent study by Lee et al [108] (2013) confirm that patients who harbor M204V strains were significantly more prone to ETV resistance than those who harbor other LAM resistance mutational patterns -rtM204I or rtA181T.…”
Section: Mutationsmentioning
confidence: 93%
“…However, in case of ETV utilization in patients with LAM treatment failure, the development of ETV resistance is more to be expected. Recent study by Lee et al [108] (2013) confirm that patients who harbor M204V strains were significantly more prone to ETV resistance than those who harbor other LAM resistance mutational patterns -rtM204I or rtA181T.…”
Section: Mutationsmentioning
confidence: 93%
“…However, as shown in previous studies, LAM-resistant HBV patients with the rtM204V mutation had the highest risk of developing ETV resistance compared with those with the rtM204I mutation (Lee et al, 2013). In addition, the rtL229F mutation effectively restored the replication capacity of the rtM204I strain compared with the rtL229W/M/V (Ji et al, 2012).…”
Section: Discussionmentioning
confidence: 53%
“…This could be due to different prevalence of baseline rtM204V mutations between Tenney's (37/57) and our (12/22) cohort. In a separate study, we found rtM204V to have a higher risk of entecavir resistance compared with rtM204I mutation (60% vs 0%, p=0.045) 5. This finding may play an important role in patients who are tenofovir-intolerant or develop tenofovir-related nephrotoxicity, hypophosphatemia and Fanconi syndromes, which occurs in up to 13%, 10% and 2% of treated patients, respectively 6 7.…”
mentioning
confidence: 77%